CLINICAL RELEVANCE OF AMBULATORY BLOOD PRESSURE MONITORING IN WOMEN WITH METABOLIC SYNDROME IN II TRIMESTER OF PREGNANCY - O. A. Lee (Klinicist)
Aim – evaluation of ambulatory blood pressure monitoring (ABPM) in pregnant women with metabolic syndrome (MS) in the II trimester, revealing their relationship with specifics of endothelial function, and determinationof possible predictor values of some indicators of ABPM in the development of preeclampsia and placental insufficiency.Materials and methods. Evaluation ABPM results performed in 82 pregnant patients with MS and 20 healthy pregnant women at 16–22weeks of gestation.\Results. More than in 50 % of surveyed patients common nature of MC hypertension was confirmed, which was manifested in a moderate increase in their blood pressure with a abnormality of its circadian rhythm. The presence of these symptoms correlated with hypertension in patients with new-onset abnormality of endotheliumependent vasodilatation in reactive hyperemia of brachial artery.Conclusion. Negative predictor role of the daily blood pressure index concerning development of preeclampsia and placental insufficiency inthe future was established.